PROTOTIPE SISTEM INFORMASI LAPORAN AFTER SALES MAINTENANCE SUPPORT - Herdiansah, Arief (JISA(Jurnal Informatika dan Sains), 2019)
The after sales maintenance support report information system prototype is an application prototype developed to be able to help the support team report their technical work activities while doing after sales maintenance support. The faster the reporting provided by the support team to the project admin, will make it easier for a project manager to analyze the status or condition of the project being handled, so that the project manager can make project status reports for company managerial needs and reports to customers. This study uses elicitation methods in analyzing user needs and using UML in the system design process. The system development process used in this study is a prototype model for then the resulting system is tested using the black box testing method. The programming language used is PHP and uses MySql as a database. The Prototype after sales maintenance support report information system created in this research has been tested on one of the projects owned by PT MTI Tiga and according to the user has been able to simplify the reporting process of after sales maintenance support activities carried out by the support team.